The Effectiveness of Communicative Approach in Teaching Present Tense to Vocational College Students: An Experimental Study - Siregar, Sri Handayani (English Teaching and Linguistics Journal (ETLiJ), 2024)
This experimental study examined the impact of a communicative approach on students' present tense mastery using a one-group pretest-posttest design. The sample comprised 70 first-semester students at Politeknik Kesehatan YRSU Dr. Rusdi Medan (2022/2023), selected through random sampling. After implementing the communicative approach treatment, test results indicated a significant improvement in present tense proficiency, with 37 students (52.8%) achieving mastery and 33 students (47.2%) requiring further instruction. Statistical analysis revealed a p-value of 0.05, confirming the effectiveness of the communicative approach in enhancing students' present tense abilities. The findings demonstrate the potential of communicative methods for grammar instruction in vocational education contexts.